Bacterial testing of platelets – has it prevented transfusion‐transmitted bacterial infections in Australia?. Issue 1 (26th September 2017) - Thyer, J.; Perkowska‐Guse, Z.; Ismay, S. L.; Keller, A. J.; Chan, H. T.; Dennington, P. M.; Bell, B.; Kotsiou, G.; Pink, J. M.
Abstract : Background and Objectives: Australia introduced bacterial contamination screening (BCS) for platelet components in April 2008. This study presents analysis performed to assess the efficacy of testing. Materials and Methods: Seven‐day aerobic and anaerobic culture is performed using the BacT/ALERT 3D system. Following an initial machine positive (IMP) flag, all associated components are recalled, and/or clinicians treating already transfused patients are notified. IMPs are categorized as 'machine false positive', 'confirmed positive' or 'indeterminate' depending on culture results of initial and repeat samples. Results: Between 2010 and 2012, 1·1% of platelet donations tested IMP; since 2013, this rate has fallen to 0·6% through improved instrument management, reducing false‐positive IMPs but maintaining sensitivity for cultures yielding bacterial growth. On average, 66% of confirmed positive and indeterminate platelet units had been transfused at the time of detection. The majority (95%) of these grew Propionibacterium sp., a slow‐growing organism that rarely causes sepsis in the transfusion setting. The incidence of reported transfuion‐transmitted bacterial infection (TTBI) has fallen since the introduction of BCS, with a 4·2‐fold [0·5, 28·2] lower rate from platelets. Conclusion: BCS has been successful in detecting platelet units containing pathogenic bacteria. The incidence of TTBI from platelets has fallen since the introduction of BCS, but the risk has not been eliminated due to rare false‐negative results. In the absence of a pathogen inactivation system for red blood cells, BCS provides 'surrogate' testing of red blood cells from which platelets have been manufactured.